DESIGNING OF MULTIFUNCTIONAL EV CHARGER BASED ON SOLAR PV ARRAY - Anusha, S.; Nagabhushanam, K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A grid operated by a sunlight concentrator system is developed for a domestic electric vehicle (EV) charger in this paper, it meets the requirements of an electric vehicle, home loads, and the grid. The charger will run independently, employing a solar panel to give uninterruptible charging and control of home loads. The grid connected mode of operation is available in the absence of a Photovoltaic panel or when the Photovoltaic module's power is unsatisfactory. In addition, the charger is assisted by the synchronized and smooth phase shifting control, which allows it to immediately connect and disconnect from the grid, neither interfering with EV charging nor home supplies. Moreover, the battery is allowed to support grid and vehicle-to-home (V2H) power transmission with vehicle-to-grid (V2G) active/reactive power support to support local loads in island conditions. The battery is often regulated to perform as an active power filter, ensuring that the grid current has a unity power factor (UPF) and a total harmonic distortion (THD) of less than 5 percent. The battery is intended for use with a 1 − ∅ 230V 50Hz and by using MATLAB/Simulink software to validate the simulation results.